Policies, Practices of Teacher Education Institutions and the Performance of their Graduates - V. Alfonso, Dr. Norman (International Journal of English Literature and Social Sciences (IJELS), 2019)
Abstract: The research study is about Policies, Practices of Teacher Education Institutions (TEIs) in the province of Nueva Ecija, Philippines and the Performance of their Graduates in the Licensure Examination for Teachers (LET). The respondents are deans/head, teachers, and teacher education graduates or passers of the 12 respondent TEIs. The study was conducted within the first semester of the Academic Year 2018–2019. Descriptive research design was used in the study with quantitative and qualitative method. The 12 TEIs were identified through purposive sampling technique while the teachers and education graduates were thru simple random sampling. Questionnaires and interview guide were utilized as the main data gathering instruments. Based on the findings of the study, the following were drawn conclusions: TEIs are cognizant that admission, retention, and LET preparation policies are important academic guidelines or procedures. Equally, TEIs are mindful that academic policies are vital means to establish and maintain quality instruction to BEEd students; Most TEIs failed to address their academic problems considering that their BEEd LET results were below the national passing rate during 10 consecutive examinations from years 2013-2017. Also, the Commission on Higher Education failed to observe or impose its policies concerning the persistent below national passing rate performance of TEIs in BEEd LET. TEIs’ admission, retention, and LET preparation policies are big contributory factors towards a healthier LET performance for BEEd; and TEIs recognize the importance of achieving BEEd LET result that is above the national passing rate through the various practices they implement. Similarly, TEIs are aware of the possible legal and business consequences in case they failed in every examination. Lastly, TEIs are mindful that LET performance of their graduates is a measure or indicator of quality academic practices and processes. Based on the conclusions of the study, the following are the recommendations: Implementation of Academic Policies, Creation of Distinct Academic Policies, Regular Revisiting of Curricula, and Institutionalization of LET Preparation Programs.